THE TURKISH CONCEPT OF â€œMINORITIESâ€ â€“ AN IRREMOVABLE OBSTACLE FOR JOINING THE EU? - Kunnecke, Arndt (European Scientific Journal, ESJ, 2014)
Fifty years ago, on 12 September 1963, the association agreement between the European Economic Community (EEC) and Turkey was signed in Ankara. However, in contrast to many other countries who applied later on, Turkey has not yet become a member of the EU. Nevertheless, Turkey’s candidacy to join the EU is still one of the most considerable and controversial topics within the European political arena. Within the accession negotiations, apart from human rights, the Kurdish and the Cypriot issues, one of the greatest challenges to Turkey’s successful candidacy is the issue of respect for and protection of minorities. It might indeed represent an unsolvable problem, which will ultimately block Turkey joining the EU. Neither the EU nor Turkey has really come to terms or dealt with what the EU sees as an "unsatisfactory" protection of minorities in Turkey. What lies at the root of this disagreement is what the term "minority" actually means. Due to Turkey’s own nation state concept as being a united and undivided country and to the terms of the Treaty of Lausanne signed in 1923, which defined Turkey as a nation, the country only recognises non-Muslim minorities such as the Greek, Armenian and Jewish populations. In contrast, the EU concept of minority includes ethnic, linguistic and religious minorities. According to the author, the most promising approach to deal with this unreconciled conceptual difference is the introduction of the "ethnic group" concept. Ethnic groups could form a sub-identity of Turkishness and help build a legal basis to the treatment of minority groups founded on human rights, which would be compatible with both Turkish and EU Law.